HIV-1 Transcription but Not Intact Provirus Levels are Associated With Systemic Inflammation. (19th October 2020) - Olson, Alex; Coote, Carolyn; Snyder-Cappione, Jennifer E; Lin, Nina; Sagar, Manish
Abstract: Individuals infected with human immunodeficiency virus (HIV) 1 have increased inflammation, which has been associated with age-associated diseases. Plasma markers, cell-associated virus levels, and ability to stimulate RNA transcription in latently infected cell lines was examined in younger and older HIV-1–infected individuals with suppressed virus. Cell-associated RNA, but not intact provirus level, had positive correlation with plasma D-dimer levels. Compared with the younger group, the older group had higher D-dimer levels and a trend toward more cell-associated RNA but similar levels of intact proviruses. Even though all measured inflammatory markers were relatively higher in the older group, this greater inflammation did not induce more HIV-1 transcription in latently infected cell lines. Inflammation and HIV-1 RNA expression increase with age despite similar levels of intact infectious HIV DNA. While plasma inflammation is correlated with HIV-1 RNA expression in peripheral blood mononuclear cells, it does not induce HIV-1 transcription in latently infected cell lines. Abstract : Plasma inflammation increases with aging in treated people with human immunodeficiency virus (HIV), is associated with intracellular HIV-1 RNA levels but not with the number of intact infectious proviruses, and does not stimulate greater HIV-1 RNA transcription in cell lines.